THE EFFECTIVENESS OF SKIMMING – SCANNING STRATEGY IN IMPROVING STUDENTS’ READING COMPREHENSION AT THE SECOND GRADE OF SMK DARUSSALAM MAKASSAR - Andi Asmawati (Universitas Islam Negeri Alauddin Makassar, 2015)
The objective of this research is to find out the effectiveness of Skimming-Scanning Strategy in improving students reading comprehension. It covered students’ literal, inferential, critical comprehension in three types of text. They were narrative, descriptive, and news item texts. The research applied quasi experimental design. The subject of the research was the second grade students of SMK Darussalam Makassar. The data collected were the students’ reading achievement through test (pretest and posttest). This research was divided into two groups, experimental and control group, the groups consisted of 28 and 27 students, respectively. The result of the data analysis showed that t-test was higher than t-table (6.373>2.000) or P-value (Sig.) was smaller than alpha (0.000 < 0.05). It meant that mean score of the experimental group was higher than the control group.